INCOME ANALYSIS ON SEA TRANSPORTATION BUSINESS ROUTES LASIWA-AMOLENGO BEFORE THE OPERATION OF THE FERRY SHIP IN THE REGENCY OF NORTH BUTON - Muhammad Syaiful; Abdullah Igo Baran Daiona; Rinto Gunadhi (Universitas Muhammadiyah Kalimantan Timur, 2021)
One of the crossing routes that has helped build the regional economy in Southeast Sulawesi is the sea transportation route from Lasiwa Village, North Buton Regency to Amolengo Village to move goods and people between the regions. The development of this sea transportation business indirectly has a role in increasing income for the local community.This study was conducted with the aim of knowing and analyzing the income of the sea transportation business on the Lasiwa-Amolengo route before the operation of the ferry in North Buton district using primary data and secondary data. To find out and analyze the Sea Transportation Business on the Lasiwa-Amolengo route in North Buton Regency, a benefit cost analysis will be carried out from revenue and costs.. The results obtained that the sea transportation business carried out by 6 (six) entrepreneurs in Wakorumba District is one of the sea transportation service businesses that supports the mobilization of goods and people. The results of the analysis show that the average sea transportation service business income reaches Rp. 8,105,452.00 per month. The level of income earned by business actors is influenced by the price (fare), the number of passengers and the number of goods. Thus, the amount of income earned is the result of operations in the sea transportation sector which in turn will increase the family income of these business actors. In addition, it can provide benefits for people who cross the route. For the North Buton government, they need to think about the fate of business actors who use small boats because with the ferry, their business will be threatened to stop because passengers are more dominant will prefer to use ferry services.